1993
DOI: 10.1038/365756a0
|View full text |Cite|
|
Sign up to set email alerts
|

MIF is a pituitary-derived cytokine that potentiates lethal endotoxaemia

Abstract: Cytokines are critical in the often fatal cascade of events that cause septic shock. One regulatory system that is likely to be important in controlling inflammatory responses is the neuroendocrine axis. The pituitary, for example, is ideally situated to integrate central and peripheral stimuli, and initiates the increase in systemic glucocorticoids that accompanies host stress responses. To assess further the contribution of the pituitary to systemic inflammatory processes, we examined the secretory profile o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
874
0
7

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 956 publications
(912 citation statements)
references
References 24 publications
31
874
0
7
Order By: Relevance
“…3,10 Since the molecular cloning of MIF, 11 this cytokine has been reevaluated as a proinflammatory cytokine and pituitaryderived hormone that potentiates endotoxemia. 12,13 It has been shown that T cells and macrophages secrete MIF in response to various proinflammatory stimuli such as endotoxins. 4 It is evident that the mechanisms of hair follicle dysfunction in AA are immunological and controlled by activated T cells.…”
Section: Discussionmentioning
confidence: 99%
“…3,10 Since the molecular cloning of MIF, 11 this cytokine has been reevaluated as a proinflammatory cytokine and pituitaryderived hormone that potentiates endotoxemia. 12,13 It has been shown that T cells and macrophages secrete MIF in response to various proinflammatory stimuli such as endotoxins. 4 It is evident that the mechanisms of hair follicle dysfunction in AA are immunological and controlled by activated T cells.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA analysis of MIF in the supernatants of cultured wtMEFs showed that maximal constitutive MIF secretion was measurable 4-8 h after medium change (3.3-6.3 ng/ml produced by a 200 000 cell culture), with secretion plateauing thereafter. As rMIF is somewhat less potent than endogenously produced MIF (Bernhagen et al, 1993), this concentration roughly corresponds to the optimum of the rMIF dose-response curve (50 ng/ml). In fact, a 20 min incubation with media from 4 h cultures of wtMEFs triggered Akt activation similar to 50 ng/ml activate Akt signaling in an autocrine manner, whereas MIF is also able to rapidly 'de novo' activate this pathway.…”
Section: Phosphorylation and Activation Of Akt By Mif And Dependence mentioning
confidence: 99%
“…In fact, MIF is prestored intracellularly and released upon stimulation, but also continuously by cycling tumor cells (Bernhagen et al, 1993;Mitchell and Bucala, 2000;Flieger et al, 2003). Activation of sustained ERK signaling is mediated by autocrine MIF action (Mitchell et al, 1999).…”
Section: Phosphorylation and Activation Of Akt By Mif And Dependence mentioning
confidence: 99%
See 2 more Smart Citations